EVALUASI KUALITAS SISTEM PERENCANAAN PEMBANGUNAN BERBASIS E-MUSRENBANG KABUPATEN MUSI BANYUASIN - Hutrianto -; Ade - Putra (Jurnal Sistem Informasi, 2017)
Evaluation of the quality of e-Musrenbang at the Badan Perencanaan Pembangunan Daerah (Bappeda) of Musi Banyuasin Regency is done by using webqual instruments consisting of usability quality(X1), information quality(X2) and interaction quality(X3). webqual is used as an appraisal instrument because the webqual emphasizes the assessment of information systems viewed from the point of view of the end user. The results of the validity test of Pearson Corellation value and by looking at the Corrected Item - Total Corellation value which is above 0.6 or equal to 0.6 and reliability test results in the chronbach's alpha value above 0.60. and the result of hypothesis for variable usability quality in correlation coefficient of 0.561 which means the assessment of Usability Quality (X1) has a relationship or a close influence on Overall Impression (Y), the result of variable hypothesis Information Quality (X2) 0.563 correlation coefficient meaning assessment has a relationship or a strong influence on the Overall Impression (Y), and the result of the hypothesis of the variable Interaction Quality (X3) correlation coefficient of 0.555 which means the assessment has a close relationship or influence on the Overall Impression (Y). Overall question items on each of the variables used are linked and directly affect the facilities and features of the E-Musrenbang System that have been developed and have received good response from the user operators in each service in the environment Regional Development Planning Board (Bappeda) of Musi Banyuasin Regency